Effect of Black Rice Bran ‘Sembada Hitam’ on T47D Breast Cancer Cells: Effect of Black rice bran on T47D - Cios Conara , Flafiani; Oktavya, Galuh; Asih Purwestri, Yekti; Nuriliani, Ardaning (Journal of Tropical Life Science, 2023)
Indonesians have a rich tradition of incorporating black rice into their diet as a functional food due to its high antioxidant content. This research investigates the effects of the ethanolic extract of "Sembada Hitam" black rice bran on T47D breast cancer cells, specifically its cytotoxic, cell growth, and apoptotic induction properties. The MTT assay method was used to evaluate the cytotoxicity of the black rice bran extract on T47D cells after 24 and 48 hours of incubation. The acridine orange/propidium iodide (AO/PI) dye double staining method was employed to assess the apoptosis-inducing properties of the extract. Additionally, a cell growth assay was conducted to evaluate the effect of the extract on cell growth, with observations recorded on days 0, 3, and 6. The results revealed that the ethanolic extract of black rice bran "Sembada Hitam," when administered at various concentrations ranging from 7.81 to 1000 µg/mL, did not exhibit cytotoxic effects on T47D cells during the 24 and 48 hours of incubation. The cell growth assay revealed that T47D cells treated with the ethanolic extract of "Sembada Hitam" black rice bran at concentrations of 250 and 500 µg/mL exhibited lower growth rates than the 1% DMSO group from the 3rd to 6th day after incubation. The ethanolic extract of "Sembada Hitam" at concentrations of 250, 500, and 1000 µg/mL resulted in cell death of 10.64 ± 2.98%, 9.99 ± 5.87%, and 5.84 ± 0.78%, respectively. In conclusion, this study found that the ethanolic extract of "Sembada Hitam" black rice bran did not demonstrate significant cytotoxic effects on T47D breast cancer cells and is, therefore, unlikely to be a suitable candidate for an anti-cancer agent.